Silent policymakers in Aotearoa New Zealand: reflections on research of early childhood teacher views on policy, practicum and partnership. Issue 1 (1st January 2018) - Gibbons, Andrew; Tesar, Marek; Steiner, Sarah; Chan, Samantha
ABSTRACT: This paper reports on the importance of the stories and perspectives of early childhood education Associate Teachers (ATs) at a time when there is considerable flux being experienced in the Aotearoa New Zealand early childhood sector, due in particular to the ongoing impact of changes in government funding policy, ongoing debates about pathways into the teaching profession, and an updated curriculum framework. The paper developed out of a research project that asked Associate Teachers (AT) about their views on the impact of recent national education policy changes. The views of ATs provide an influential voice for the sector, and particularly for teacher education providers through the student teacher practicum experience. Evidence and analysis of AT views provides insight into how the triadic of student, lecturer and practitioner can work together to support student teachers with their practicum experience in relation to the recent policy changes. A very small return rate for online questionnaires left the research team with the challenge of talking about the meaning of such silence, while at the same time acknowledging and valuing the views of those who did complete the questions. The paper presents a shift in the researchers' perspectives on the subject of their research, and raises awareness of the problem of working with, and being committed to, the silent voices. The paper concludes with foundations for future research, focusing on ATs as active participants in teacher education policymaking and involving them both as researchers and participants.